Shifts in Xanthomonas spp. causing bacterial spot in processing tomato in the Midwest of the United States. Issue 5 (3rd September 2022) - Rotondo, F.; Bernal, E.; Ma, X.; Ivey, M. L. Lewis; Sahin, F.; Francis, D. M.; Miller, S. A.
Abstract: Bacterial spot (BST) is a highly impactful disease of open-field tomatoes produced in the U.S. Midwest. We combined BST survey data from 2010 to 2013 and 2017 to 2020 from midwestern states to characterize BST-causing Xanthomonas species associated with processing tomatoes. We identified 1009 Xanthomona s spp. strains and characterized their temporal/geographical distribution, bactericide resistance, and bacteriocin production. This work highlights a notable shift in species associated with BST in the study region from X. hortorum pv. gardneri to X. perforans over the course of the surveys. While the frequency of X. perforans associated with BST increased overall, some regions remained dominated by X. hortorum pv. gardneri, possibly due to the impact of seed or transplant source or local environment. No significant association was found between fruit maturity and Xanthomonas species isolated, suggesting no impact on the observed species shift. While in vitro screening demonstrated an increase in copper resistance for all Xanthomonads over time, and to a lesser degree streptomycin, no significant association with resistance and Xanthomonas species was identified, suggesting no association with the observed population shift. Finally, while nearly half of all X. perforans strains isolated produced bacteriocins, these antimicrobial compounds were found to have no impact on X. hortorum pv. gardneri strains and are not likely responsible for the observed species shift. However, the rise in bacteriocin-producing X. perforans strains may be linked to the disappearance of X. euvesicatoria in Midwest processing tomato production, although this will require further investigation.